ANALISIS KEANDALAN BUCKET ELEVATOR MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) UNTUK MENURUNKAN DOWNTIME PRODUKSI DI PT XYZ: ANALISIS KEANDALAN BUCKET ELEVATOR MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) UNTUK MENURUNKAN DOWNTIME PRODUKSI DI PT XYZ - Muhammad Irwan Irwan; Roberth M Ratlalan; Dimas Adrian (Jurnal Teknologi Dan Riset Terapan (JATRA), 2026)
Bucket elevator is a material handling system that plays a critical role in maintaining production continuity at PT XYZ. Continuous operation makes this equipment prone to failures that directly contribute to increased production downtime. This study was conducted to evaluate the reliability of the bucket elevator and to determine an effective maintenance strategy by integrating the Reliability Centered Maintenance (RCM) and Failure Mode and Effects Analysis (FMEA) methods. The analysis was conducted using downtime data and failure history from March to August, with the March–May period representing the condition before RCM implementation and June–August representing the condition after RCM implementation. The analysis showed that the belt was the most critical component, with an initial total downtime of 870 minutes and the highest Risk Priority Number (RPN) value of 378, associated with the belt tear failure mode. Based on the RCM–FMEA results, maintenance strategies were formulated with a primary focus on critical components. The implementation of RCM reduced the total bucket elevator downtime from 1245 minutes to 465 minutes, corresponding to a reduction of 62.65%. These results demonstrate that Reliability Centered Maintenance is effective in improving equipment reliability and reducing production downtime at PT XYZ.